Development of Islamic Religious Education Comic Media: A Script Cooperative Learning Model - Tiur Rianiroha Siregar; Mukhtar Mukhtar; Farihah Farihah (RIRAI Publisher, 2024)
This research aims to develop learning media in the form of Islamic Religious Education comics with the material I Believe in the Prophets and Apostles, which is used as a very practical learning medium for grade 4 students of MIS Muhajirin Medan Polonia. Research and development methods use the ADDIE model. This development stage includes analysis, design, development, implementation, and evaluation. The development process was carried out with input from material experts, media experts, and learning design experts, practicality testing by students, and effectiveness testing. The results of the research show that: (1) learning media in the form of Islamic Religious Education comics with the Cooperative Script model obtained a material expert score of 4.51, media expert 4.54 (very high), and learning design expert 4.77 (very high). Field trials of learning media in the form of comics obtained an average score of 4.50 (very high). Guidance and information aspect 4.60 (very high), media material aspect 4.43 (very high), evaluation aspect 4.40 (very high), media and facility design aspect 4.48 (very high), and pedagogical effect aspect 4.60 (very high). The values obtained indicate that the product developed is very feasible. (2) Test the effectiveness of media in the form of Islamic Religious Education comics with the cooperative script learning model using the N-Gain Score formula. The research results showed a figure of 0.58 (medium effectiveness). The research conclusion is that the Islamic Religious Education comic media, the cooperative script learning model, is suitable for use and effective in improving learning outcomes.